The Influence of Social Media Marketing and Celebrity Endorsements on Consumer Purchase Intention in Makassar City - Amalia Febeka Prianggani; Pemilia Sulistyowati (MANAJEMEN, 2026)
This research aims to determine the impact of social media marketing and celebrity endorsements on the purchase intention of skincare products in Makassar. This research uses a quantitative approach. The population in this research is all potential consumers who have a purchase interest in skincare products in Makassar. The sample in this research amounted to 60 respondents taken by convenience sampling method. Data collection used a questionnaire measured on a Likert scale of 1-5 points. Data analysis used multiple linear regression and the data was processed using SPSS version 30. The results of partial testing showed positive and significant results of social media marketing and celebrity endorsement variables on the purchase intention of skincare products in Makassar. The results of simultaneous testing, social media marketing and celebrity endorsement variables were able to significantly explain variations in employee performance on the purchase intention of skincare products in Makassar.